An experimental study of the effects of dressing parameters on the topography of grinding wheels during roller dressing. (January 2018) - Palmer, Jack; Ghadbeigi, Hassan; Novovic, Donka; Curtis, David
Abstract: Vitreous-bonded grinding wheels are widely used for machining features on aerospace components achieving high material removal rates under high pressure coolant. Dressing is a vital stage in the grinding process to ensure a consistent wheel topography and performance. However, the effects of roller dressing on functional performance of vitreous grinding wheels as well as its influence on different abrasive grit morphologies have not been fully characterised. This paper studies the influence of dressing parameters on the topography, morphology and characteristics of the surface of different vitrified abrasive wheels in order to better understand the process and therefore optimise the preparation of grinding wheels for industrial machining. Alumina grinding wheels with conventional and engineered grit shapes were dressed at two different infeed rates over a range of seven different speed ratios (from −0.8 to +1). An experimental methodology has been developed incorporating a range of known techniques to define the abrasive wheel condition including measured power consumption and ground graphite coupons as well as using optical microscopes to measure grain fracture flats, peak density and abrasive grain shape. It has been found that power consumption of the grinding wheel spindle increases at higher infeed rates and speed ratios. This leads to increased fracturing of the grains and whole-grain pull out. According to the results the infeed rate has a more substantial effect on wheel topography than speed ratio and the response of engineered grit morphologies to dressing is dependent on grit orientation.